Operational efficiency of pharmaceutical companies in China: based on three-stage DEA with undesirable outputs - Sun, Jiaqiang; Rosli, Anita; Daud, Adrian (Multidisciplinary Digital Publishing Institute (MDPI), 2025)
After a period of rapid growth, China’s pharmaceutical industry is facing multiple challenges, including insufficient innovation and severe pollution. Current research on the efficiency of pharmaceutical companies in China primarily focuses on financial or innovation aspects. Therefore, a holistic approach to operational efficiency is needed. To measure the operational efficiency of pharmaceutical companies in China more accurately and holistically, while accounting for environmental pollution, this study employs a three-stage Data Envelopment Analysis (DEA) model with undesirable outputs to evaluate efficiency across five dimensions: market performance, profitability, financial risk control, innovation, and sustainability. This approach integrates financial, innovation, and sustainability indicators to provide a more industry-specific framework for efficiency measurement. Furthermore, integrating with Stochastic Frontier Analysis (SFA) allows for revealing the impact of environmental factors on efficiency. The results show that both technical efficiency (TE) and pure technical efficiency (PTE) are relatively low in the first and third stages, with significant regional disparities. After excluding environmental factors, some regions—typically economically developed areas—showed improved overall efficiency. This indicates that the local environment in these regions is not conducive to the development of pharmaceutical enterprises. The SFA results further demonstrate that investments in education and high-level talent significantly enhance efficiency, whereas pollutant emissions and per capita income reduce operational efficiency. The findings suggest that local governments should enhance the operational efficiency of pharmaceutical enterprises by investing in education, attracting skilled talent, and improving waste infrastructure. Additionally, less efficient firms are encouraged to optimize resource allocation to achieve higher efficiency.